Planning the Needs of Educational Facilities and Infrastructure in the Context of Improving the Quality of Education at PKBM Al Ghoutsillah, Batu Tunau Village - Abduh, Muhamad; Yahyadin, Muhammad; Ahdar, Muhammad; Rusidah, Rusidah; Sulistiyana, Sulistiyana (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the planning of educational facilities and infrastructure needs at PKBM Al Ghoutsillah as a strategic effort to enhance the quality of education. Adequate facilities and infrastructure are essential components in creating an effective learning environment and supporting the achievement of educational objectives. This research employs a qualitative approach with data collected through observations, in-depth interviews, and documentation involving administrators, tutors, and learners. The findings reveal that the planning process is carried out through identifying learner needs, mapping curriculum requirements, and evaluating the condition of existing facilities. Despite facing financial limitations and resource constraints, PKBM Al Ghoutsillah strives to meet the minimum standards of learning facilities by optimizing internal resources, prioritizing procurement based on urgency, and establishing collaborations with various partners. The study shows that structured and adaptive planning contributes to improved student engagement, increased learning effectiveness, and better overall educational service quality. Furthermore, the research provides significant implications for PKBM management development, particularly in strengthening procurement policies, facility maintenance strategies, and collaborative initiatives to support the sustainability of non-formal education services.